2017
DOI: 10.1186/s11671-017-2391-3
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite Solar Cells Fabricated by Using an Environmental Friendly Aprotic Polar Additive of 1,3-Dimethyl-2-imidazolidinone

Abstract: Perovskite solar cells (PSCs) have great potentials in photovoltaics due to their high power conversion efficiency and low processing cost. PSCs are usually fabricated from PbI 2 /dimethylformamide solution with some toxic additives, such as N-methyl pyrrolidone and hexamethylphosphoramide. Here, we use an environmental friendly aprotic polar solvent, 1,3-dimethyl-2-imidazolidinone (DMI), to fabricate perovskite films. By adding 10 vol% DMI in the precursor solution, high-quality perovskite films with smooth s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Moreover, some synthetic routes for highly efficient perovskites employ antisolvents 31,32 (e.g. chlorobenzene or toluene) and the treatment of precursors solution with additives, such as hexamethylphosphoramide 33 and 1,3-dimethyl-2-imidazolidinone, 34 as well as the use of solvent blends. 35 Various studies have been carried out on the solution chemistry of the perovskite precursors, 16,[36][37][38][39][40][41][42][43][44][45] Accordingly, in the present manuscript we investigate the chemistry of typical precursor solutions employed for LHPs synthesis by a combined experimental and computational approach.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some synthetic routes for highly efficient perovskites employ antisolvents 31,32 (e.g. chlorobenzene or toluene) and the treatment of precursors solution with additives, such as hexamethylphosphoramide 33 and 1,3-dimethyl-2-imidazolidinone, 34 as well as the use of solvent blends. 35 Various studies have been carried out on the solution chemistry of the perovskite precursors, 16,[36][37][38][39][40][41][42][43][44][45] Accordingly, in the present manuscript we investigate the chemistry of typical precursor solutions employed for LHPs synthesis by a combined experimental and computational approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, the DMI solvent is a marginal solvent for PbI 2 +MAI precursors and can only be introduced as a solvent additive with a small amount into the DMF system. The resultant PCE of the related solar cells was less than 15% [ 23 ]. In contrast, we found that the perovskite precursors Pb(Ac) 2 and MAI have a high solubility in the DMI solvent, which can be evidenced from the yellow transparent solution ( Figure 1(a) ).…”
Section: Resultsmentioning
confidence: 99%
“…A urea molecule as a coordinating additive was added to the MAPbI 3 precursor solution to form compact perovskite films as reported by Lee et al The urea additive induces large grain size of perovskite films due to increased activation energy as illustrated in Figure b. Based on the same principle, 1,3‐dimethyl‐2‐imidazolidinone (DMI) with low volatility was also used as an additive to form compact perovskite films . Han et al reported an additive of methylammonium thiocyanate (MASCN), which was added as a precursor to achieve high‐quality MAPbI 3 films; the process is shown in Figure c.…”
Section: Solution Methods For Perovskite Film Fabricationmentioning
confidence: 94%